Application of Zakat Accounting at Amil Zakat Institutions (Case Study on Laz Washal, North Sumatra) - Shofi Alizha Putri; Yenni Samri Juliaty Nasution (Journal of Indonesian Management, 2022)
The word zakat etymologically has many meanings: holy, best and clean. In terms of terminology, zakat is a certain amount of disturbance that is required by Allah to be given to those who are entitled. Based on the Zakat Processing Norms No. 38 of 1998, the definition of Zakat must be set aside so that it can be given to Muslims or Muslim-owned organizations to those who have their rights according to religious rules. The data sources for this research are primary data and secondary data. Primary data can be obtained directly from the main source of information, namely LAZ WASHAL in North Sumatra, and data will be obtained through interviews. Secondary data is in the form of books, but explanations and content analysis are carried out. Survey description uses data collection techniques to describe survey data or results. The data collected were analyzed using descriptive methods and qualitative analysis. In this research, the analysis conveys the situation in Razwashal, North Sumatra and the application of Zakat accounting in Razwashal, North Sumatra. Settlement of Zakat funds by Laz Washal North Sumatra is cash basis, the model for recording accounting transactions must record all income reports according to PSAK No. 109, and Laz Washal must prepare financial statements in accordance with PSAK.